Indonesia's Foreign Policy in Dealing with Non-Traditional Threats (Case Study Drugs Trafficking in Indonesia) - Rinaldi, M.; Pedrason, Rodon; Wirajuda, Muhammad Hadianto (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia is the largest archipelago in the world, located in Southeast Asia. With an area of more than 1.9 million square kilometers, Indonesia has more than 17,000 islands. Indonesia is a target for drug trafficking due to its geography as an archipelago and an important transit route in Southeast Asia. On the issue of drug trafficking in Indonesia, the Indonesian government has taken seriously the threat posed by drug trafficking and is committed to tackling this problem. In dealing with this non-traditional threat, especially drug trafficking, defense diplomacy and international cooperation are important in dealing with drug trafficking. This cooperation can take the form of information exchange, joint countermeasure strategies, and coordination of action against drug syndicates. Indonesia's foreign policy has an important role in addressing the non-traditional threat of drug trafficking, To face this challenge, countries must work together in various aspects. Indonesia's foreign policy in dealing with the non-traditional threat of drug trafficking is based on international cooperation and diplomacy. Indonesia has been actively cooperating with other countries, including through regional frameworks such as ASEAN, to address drug trafficking challenges.